Perancangan dan Pengembangan Vıdeo Profıl Lulusan Animator untuk PS Sistem Informasi dengan Teknık Motion Graphic - Deli Deli; Rino Rino (Conference on Business, Social Sciences and Technology (CoNeScINTech), 2021)
Undergraduate Program (UP) Information System is a higher education program which begin in 2000 to hold a Computer science education program in Batam area. These days, information systems is growing rapidly, One of them is the development of various kinds promotion media such as video profile. In this Job Training (KP), the result to be achieved is a video profile of an animator, who was graduated from Batam International University (UIB) Bachelor of Information Systems Study Program. This video profile will be created using Motion Graphic Technique. The Output in the form of video profile will be implemented through a website called Youtube